2020
DOI: 10.3389/fbioe.2019.00475
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Regulatory Genes and Metabolic Processes Important for Alginate Biosynthesis in Azotobacter vinelandii by Screening of a Transposon Insertion Mutant Library

Abstract: Azotobacter vinelandii produces the biopolymer alginate, which has a wide range of industrial and pharmaceutical applications. A random transposon insertion mutant library was constructed from A. vinelandii ATCC12518Tc in order to identify genes and pathways affecting alginate biosynthesis, and about 4,000 mutant strains were screened for altered alginate production. One mutant, containing a mucA disruption, displayed an elevated alginate production level, and several mutants with decreased or abolished algina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…The results of sugar consumption and alginate production were consistent with the finding of Sabra et al that most carbon sources consumed for alginate production led to a lower DO concentration, as shown in Figure S2, or an increased oxygen uptake rate, as shown in Figure S3, because of the wastage of the carbon source for respiration to reduce the oxygen concentration around the cell. , All of the cultures showed a rapid decrease in DO to near zero during early fermentation (between 2 H and 4 h) because of the accumulation of the cell growth together with the alginate synthesis, which resulted in high viscosity and low oxygen transferred in the culture . A comparison of our results (same sucrose concentration and aeration rate) obtained using an airlift bioreactor to those of Díaz-Barrera et al obtained using a stirring tank (non-nitrogen fixation) revealed that the DO profiles were similar and rapidly reduced to near zero, presenting oxygen limitation from the beginning of the fermentation.…”
Section: Resultssupporting
confidence: 90%
“…The results of sugar consumption and alginate production were consistent with the finding of Sabra et al that most carbon sources consumed for alginate production led to a lower DO concentration, as shown in Figure S2, or an increased oxygen uptake rate, as shown in Figure S3, because of the wastage of the carbon source for respiration to reduce the oxygen concentration around the cell. , All of the cultures showed a rapid decrease in DO to near zero during early fermentation (between 2 H and 4 h) because of the accumulation of the cell growth together with the alginate synthesis, which resulted in high viscosity and low oxygen transferred in the culture . A comparison of our results (same sucrose concentration and aeration rate) obtained using an airlift bioreactor to those of Díaz-Barrera et al obtained using a stirring tank (non-nitrogen fixation) revealed that the DO profiles were similar and rapidly reduced to near zero, presenting oxygen limitation from the beginning of the fermentation.…”
Section: Resultssupporting
confidence: 90%
“…In A. vinelandii however, AlgR does not affect algD transcription ( Núñez et al, 1999 ). In the case of AlgB, a recent study by Mærk et al found that a mutation in algB did not affect alginate production, which is in sharp contrast to its role in P. aeruginosa ( Leech et al, 2008 ; Mærk et al, 2020 ). In the same study, it was found that the AmrZ regulator (Alginate and Motility Regulator) is necessary for alginate production in A. vinelandii , since an amrZ − mutant reduces the production of the polymer, but the molecular mechanism of this regulation remains to be elucidated ( Mærk et al, 2020 ).…”
Section: Transcriptional Regulationmentioning
confidence: 92%
“…Alginate production is an energy and carbon demanding pathway finely regulated by the metabolic status of the cell. Mærk et al (2020) showed that in general, the synthesis of alginate requires an optimum metabolism, as disruption of genes involved in biosynthetic pathways affecting the production of vitamins, purines, or tricarboxylic acid cycle intermediates, among others, reduces or abolishes the production of this polymer. Accordingly, supplementing the culture medium with some of these compounds favors alginate production.…”
Section: Metabolic Effects On Alginate Productionmentioning
confidence: 99%
See 1 more Smart Citation